Trend of Climate and Hydrology Change in Bosten Lake Basin and Its Influence on the Lake Level - YAO Junqiang; CHEN Jing; Dilinuer Tuoliewubieke; HU Wenfeng (Renmin Zhujiang)
Bosten Lakehas experienced drastic change on water level due to the climate environment changes and intensified human activities.Based on the recent climate and hydrological data,this paper analyzes the hydrological and climatic elements and the change characteristics of the Bosten Lake Basin from 1961 to 2019,and discusses the possible influencing factors for the hydrological change of the lake.The results show that:There is obvious changes by stages on the water level (area) of the lake as follows:decrease during 1961—1987,rapid increase during 1988—2002,drastic decrease during 2003—2012,and drastic increase after 2013.The changes by stages are caused by a climate-driven regime shift coupled with human disturbance.The increase in the water level after 1987 is driven by regional climate warming and wetting.However,since 2003,due to the increase in agricultural irrigation water,the runoff of Bosten Lake is reduced;after the implementation of the ecological water conveyance project (EWCP),the lake's outflow is significantly increased;and a decreased precipitation leads to an increased drought frequency.Therefore,the lake level drops significantly under the combined action of these factors.The increase in lake level since 2013 is mainly related to the increase in the supply of melted ice and snow caused by the great increase in precipitation and temperature in mountainous areas.Furthermore,wastewater emissions give rise to water degradation,resulting in complete change on the natural water cycle system in the Bosten Lake.Indeed,under the background of climate change,the future water security of Bosten Lake is largely dependent on the human activities.